2006
DOI: 10.1007/s00262-005-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

The immunologically active site of prothymosin α is located at the carboxy-terminus of the polypeptide. Evaluation of its in vitro effects in cancer patients

Abstract: Prothymosin alpha (proTalpha) is a 109 amino acid long polypeptide presenting distinct immunoenhancing activity in vitro and in vivo. Recent reports suggest that in apoptotic cells, proTalpha is cleaved by caspases at its carboxy(C)-terminus generating potentially bioactive fragments. In this study, we identified the peptide segment of proTalpha presenting maximum immunomodulatory activity. Calf thymus proTalpha was trypsinised, and the five fragments produced (spanning residues 1-14, 21-30, 31-87, 89-102 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
1
14
0
6
Order By: Relevance
“…ProT (100)(101)(102)(103)(104)(105)(106)(107)(108)(109) induces PBMC proliferation and cytotoxicity, promotes the maturation of dendritic cells (DC), adopts a -sheet conformation, and its eVects are sequence-speciWc and comparable to that of intact proT . In an earlier study, we had shown that a slightly smaller segment (103)(104)(105)(106)(107)(108)(109) was also eVective in restoring the immune function of PBMC obtained from cancer patients in vitro [90]. As for today, the peptide TKKQKTDEDD is known to be generated in vivo upon caspase-cleavage of proT during apoptosis [91,92], and additional mechanisms of its generation and immunoreactivity are currently being investigated in our laboratory.…”
Section: A-thymosins In Cancer Therapymentioning
confidence: 94%
“…ProT (100)(101)(102)(103)(104)(105)(106)(107)(108)(109) induces PBMC proliferation and cytotoxicity, promotes the maturation of dendritic cells (DC), adopts a -sheet conformation, and its eVects are sequence-speciWc and comparable to that of intact proT . In an earlier study, we had shown that a slightly smaller segment (103)(104)(105)(106)(107)(108)(109) was also eVective in restoring the immune function of PBMC obtained from cancer patients in vitro [90]. As for today, the peptide TKKQKTDEDD is known to be generated in vivo upon caspase-cleavage of proT during apoptosis [91,92], and additional mechanisms of its generation and immunoreactivity are currently being investigated in our laboratory.…”
Section: A-thymosins In Cancer Therapymentioning
confidence: 94%
“…T2 cells were incubated for 2 h at 37°C with 10 μg/mL HER-2(9 369 ) or tyr(9 369 ), washed and labeled with sodium chromate, as previously described [21]. Non-loaded T2 were similarly labeled for controls.…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously shown that proTα upregulates the expression of IRAK-4 in human monocytes [19], ligates TLR-4 on murine macrophages and signals through MyD88-dependent and independent pathways [20]. Similar to its immunoreactive decapeptide proTα(100–109) [21], it upregulates the expression of HLA-DR [22], CD80, CD83 and CD86 and promotes maturation of human DCs in vitro [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Although its biological role has not been completely elucidated, literature points toward a dual role for ProTa: an extracellular one, associated with cell-mediated immunity (Cordero et al 1997;Skopeliti et al 2006), and an intracellular one, related to cell proliferation and apoptosis (Bustelo et al 1991;Rodriguez et al 1998;Jiang et al 2003). Increased intracellular expression of ProTa, which has been thought to be an oncoprotein (Karapetian et al 2005;Kobayashi et al 2006), has been observed in several types of human cancer.…”
mentioning
confidence: 99%